2004
DOI: 10.1023/b:joec.0000042406.76705.ab
|View full text |Cite
|
Sign up to set email alerts
|

Semiochemistry of the Goldeneyed Lacewing Chrysopa oculata: Attraction of Males to a Male-Produced Pheromone

Abstract: Gas chromatographic-electroantennographic detection (G3C-EAD) experiments showed that antennae of males and females of the goldeneyed lacewing, Chrysopa oculata Say (Co. = Chrysopa), consistently responded to four compounds extracted from the abdominal cuticle of males:nonanal, nonanol, nonanoic acid, and (1R*,2S*,5R*,8R*)-iridodial. These compounds were not detected from abdominal cuticle of females. Thoracic extracts of both sexes contained antennal-stimulatory 1-tridecene and EAD-inactive skatole. Chrysopa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 13 publications
2
57
1
Order By: Relevance
“…is skatole (3-methylindole) (Blum et al 1973;Güsten and Dettner 1991), and extended the known distribution of this foul-smelling PG compound to two additional genera of green lacewings, Plesiochrysa and Ceraeochrysa. However, earlier reports of 1-tridecene in the prothoracic gland secretions of Chrysopa oculata (Blum et al 1973;Zhang et al 2004) and Co. nigrispinus (Zhang et al 2006a) are here shown to be in error. Synthetic 1-tridecene did not coelute with the tridecene found in the PG secretions of these Chrysopa spp., whereas synthetic (Z)-4-tridecene did coelute with the natural products.…”
Section: Resultscontrasting
confidence: 64%
See 2 more Smart Citations
“…is skatole (3-methylindole) (Blum et al 1973;Güsten and Dettner 1991), and extended the known distribution of this foul-smelling PG compound to two additional genera of green lacewings, Plesiochrysa and Ceraeochrysa. However, earlier reports of 1-tridecene in the prothoracic gland secretions of Chrysopa oculata (Blum et al 1973;Zhang et al 2004) and Co. nigrispinus (Zhang et al 2006a) are here shown to be in error. Synthetic 1-tridecene did not coelute with the tridecene found in the PG secretions of these Chrysopa spp., whereas synthetic (Z)-4-tridecene did coelute with the natural products.…”
Section: Resultscontrasting
confidence: 64%
“…Green lacewing adults have long been known to communicate intraspecifically via substrate vibrations (e.g., Henry 1982), but only recently was it discovered that males in the genus Chrysopa produce aggregation pheromones from thousands of elliptically shaped glands embedded in their abdominal cuticle Zhang et al 2004Zhang et al , 2006a. Interestingly, female goldeneyed lacewings [Neuroptera: Chrysopidae: Chrysopa (= Co.) oculata Say] do not enter traps baited with pheromone (1R,2S,5R,8R-iridodial) Zhang et al 2004), presumably because females attract males via substrateborne vibrations at close range (Henry 1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The highly specific relationships of insect predators, herbivores, parasites and pollinators provide simple, readily testable models for olfactory specialization, and both behavioral methods and electro-anetennogram detection have shown that thresholds are lowered for ecologically relevant compounds. This kind of specificity is well known for conspecific pheromone components (Cabrera et al, 2001, Jintong et al, 2001, Kalinova et al, 2003, Yamamoto et al, 1999, Zhang et al, 2004, and others) Other important compounds identifying preferred prey, forage plants, oviposition sites and other important resources are also detected with higher sensitivity (Backman et al, 2000, Bichao et al, 2001, Costantini et al, 2001, Rostelian et al, 2000. Antennal detection is highly selective, discriminating very slight changes in odorant compound structure (carbon chain length, functional group, stereochemistry) that in turn reflect prey or host specificity that is in some cases very narrow, famously in the case of the human-specializing malaria vector Anopheles gambiae (Costantini et al, 2001).…”
Section: Introductionmentioning
confidence: 81%
“…In gas chromatographic-electroantennographic detection (GC-EAD) experiments, males and females of C. oculata reacted to four compounds from the abdominal cuticle of males that are absent in females Zhang et al, 2004). Both males and females were strongly attracted to iridodial, a malespecific compound of C. oculata, and aggregated near lures of this compound in nature, suggesting the possibility it could be used to increase oviposition in targeted fields (Chauhan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%